(untitled) (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY Induction of labour after previous caesarean section (CS) is a challenge for obstetricians due to the increased risk of uterine rupture. Common methods for labour induction are balloon catheters and oxytocin as they are considered safe. However, the effectiveness remains unclear as currently available data are limited. Therefore, we aimed to determine safety and effectiveness of balloon catheter or oxytocin for labour induction after CS. METHODS We included 179 consecutive women with a previous CS and labour induction in this retrospective study. We performed labour induction using a balloon catheter in case of a Bishop score of <6 and intact membranes, or oxytocin in the case of a Bishop score of >6 and/or premature rupture of membranes. The primary outcome was the rate of successful vaginal deliveries. We adjusted for multiple factors that may have impacted on the rate of vaginal delivery as well. The secondary outcomes were the rate of maternal and neonatal morbidities. RESULTS We detected a vaginal delivery success rate of 45.8% in the catheter and of 63.9% in the oxytocin group. We identified previous vaginal birth as an independent predictive factor for successful vaginal delivery in both groups. Induction using oxytocin was a negative predictive factor for neonatal admissions. Multivariate analysis showed that post-term pregnancy decreased the likelihood of vaginal delivery. We did not detect any factors predicting uterine rupture or uterine dehiscence, which occurred with similar frequency in both groups. Finally, the neonatal admission rate was less likely with higher gestational age and oxytocin as an induction method, whereas previous vaginal birth increased the risk. CONCLUSIONS Our study indicates that induction of labour with balloon catheter or oxytocin seems to be safe in women with previous CS. Labour induction using a balloon catheter in women with previous CS and unfavourable cervix has a disappointingly low success rate. We identified factors influencing vaginal delivery success rates. Women with previous CS and indications for labour induction should be informed about vaginal birth success rates and the alternative of elective repeat CS needs to be discussed.